Nutritional status and physical activity of childhood leukemia survivors - Tanjung, Conny; Lukito, Johannes Bondan; Meylani, Prima Dyarti (Paediatrica Indonesiana, 2014)
Background Acute lymphoblastic leukemia (ALL), the most common malignancy of childhood, has an overall cure rate of approximately 80%. Long-term survivors of childhood ALL are at increased risk for obesity and physical inactivity that may lead to the development of diabetes, dyslipidemia, metabolic syndrome, as well as cardiovascular dis eases, and related mortality in the years following treatment. Objective To evaluate the physical activity and the propensity for developing obesity longer term in ALL survivors. Methods This retrospective cohort study included all ALL survivors from Pantai Indah Kapuk (PIK) Hospital. We assessed their physical activity and nutritional status at the first time of ALL diagnosis an d at the time of interview. Results Subjects were 15 ALL survivors aged 7 to 24 years. The median fo llow up time was 6.4 years (range 3 to 10 years). Only 2 out of 15 survivors were overweight and n one were obese. All survivors led a sedentary lifestyle. Most female subjects had increased BMI, though most were not overweight/obese. Steroid therapy in the induction phase did not increase the risk of developing obesity in ALL survivors. Conclusion Lon g-term survivors of childh ood ALL do not meet physical activity recommendations according to the CDC (Centers for Disease Control). Howevei; steroid therapy do not seem to lead to overweight/obesity in ALL survivors.